Factors influencing individuals’ decision-making and causing financial crisis - Jurevičienė, Daiva; Skvarciany, Viktorija; Lagunavičiūtė, Austė (Journal of Business Economics and Management, 2020)
It is essential to look at financial crises from both theoretical and practical aspects, as this is an old and recurring phenomenon. However, it is still unknown how to manage their formation. The article aims at assessing the influence of individuals’ financial decisions on financial crisis formation. The interface between economic decisions made by individuals and financial crises is assessed using expert evaluation method. The multi-criteria estimation performed using the TOPSIS method to evaluate when individuals make the most irrational decisions. Moreover, finally, economic decisions rationality index is concluded, evaluating when individuals make ridiculous decisions. The rationality index of economic decisions measures the number of irrational decisions during the economic expansion. Economic decisions rationality index divided into three groups: economic factors, financial sector and psychological factors. Assessment of the irrational decisions made during the economic expansion demonstrates that during the first period (2001–2006) the least irrational decisions were made in 2001 and the most in 2004; while during the second period (2010–2017), the least irrational decisions were made in 2011 and the most in 2015. The limitation of the research is that the data is accessible only for the US; hence, the results could differ in other countries.